Foundations of education research: Understanding theoretical components - Chu, Shiao-Wei; Hussein, Ibtesam (Journal of Interdisciplinary Studies in Education, 2015)
There are lots of challenges facing novice researchers and graduate students while committing to a research design. It is common to hear that graduate students spend countless hours learning the meaning of research components and terms. Also, it is not surprising that there are many professors who struggle with finding a good research book because most textbooks seem to lack practical models, examples or discussions to guide novice researchers to understand a very wide range of research in education. Dr. Egbert and Sanden’s Foundations of Education Research: Understanding Theoretical Components fills the gap with this short, practical book containing literally examples and templates to steer both beginning and established researchers.